Use of Coffee Silverskin and Stevia to Improve the Formulation of Biscuits - Garcia-Serna Esther; Martinez-Saez Nuria; Mesias Marta; Morales Francisco J.; Castillo M. Dolores del (Polish Journal of Food and Nutrition Sciences)
Decreasing the amount of sugar added to biscuits is a good strategy to obtain a healthy product. However, a reduction in the quantity of sugar may affect its nutritional value and quality. The feasibility of the combined use of stevia and coffee silverskin for achieving healthier, nutritious and good quality biscuits has been investigated. Ten wheat four biscuit formulations were designed. Sucrose, maltitol and stevia were used as sweeteners and coffee silverskin was used as a natural colouring and as a source of dietary fbre. The quality of the biscuits was evaluated by measuring their moisture, thickness, breaking force and colour. Acrylamide (ACR) and hydroxymethylfurfural (HMF) contents were also determined in the interest of food safety. The quality and safety of the innovative biscuits was obtained by an analysis of the sugars, proteins, free amino acids, chlorogenic acid, overall antioxidant capacity and acrylamide after in vitro digestion. Only the stevia biscuits and those added with coffee silverskin extract and the solid residue recovered from the extraction process, were selected for that study. A comparison of the stevia formulated biscuits, with the stevia formula added with silverskin, showed that the added biscuits had a good nutritional quality and improved texture and colour.